Hukuman Mati: Dari Tradisi Arab Menuju Hukum Al-Qur'an - Dede Rodin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
The death penalty is the most Islamic law get resistance in its implementation. This resistance appears among others as a result of the symbolic understanding on the death penalty without understanding what and why this punishment stipulated in the Qur?an. Therefore, this article intends to answer the fundamental questions; how the concept of the death penalty in the Qur?an. This article resulted that the death penalty is one model of inculturation of the Qur?an to the existing tradition, with a change of paradigm regarding moral values and a more humane law, among others: (1) the principle of enforcement, from the original law ?vengeance? (vendetta, lex talionis, tha?r) to ?reply in kind?; (2) The motive for murder, of which initially involves all kinds of murder -including war- be designed killing and hir?bah only; (3) The prosecution, of which the extended family into the nuclear family; (4) accountability, from the collective responsibility to individual responsibility.